PELATIHAN MEDIA BERBASIS TEKNOLOGI INFORMASI: GURU BIMBINGAN DAN KONSELING KREATIF BERINOVASI - Ni Made Diah Padmi; Tri Cahyono (Jurnal Bimbingan dan Konseling Borneo, 2023)
AbstractThe results of the initial data in the previous study obtained an overview of the 3 problems found, namely teachers and students had not optimally utilized Information Technology facilities, had not been proficient enough in utilizing Information Technology applications that were useful in supporting Guidance and Counseling services, had never conducted development training Information Technology-based media for Guidance and Counseling teachers in Tarakan City. Based on the potential problems obtained, collaboration is carried out in providing training in the development of information technology-based media as a movement to increase teacher skills in utilizing Information Technology. This program is expected to improve the quality of Guidance and Counseling services. The goal is to maximize the use of Information Technology which is growing as a support for Guidance and Counseling services in schools. This activity carries mentoring material in optimizing Microsoft Powerpoint as a teaching medium and compiling an online assessment through Google Forms which was held for two days in the Meeting Room of SMP Negeri 1 Tarakan on Wednesday-Thursday, 28-29 July 2022.Keywords: Information Technology, Guidance CounselingAbstrakHasil data awal dalam penelitian sebelumnya, memperoleh gambaran adanya 3 permasalahan yang ditemukan yaitu guru dan Mahasiswa belum secara optimal memanfaatkan sarana Teknologi Informasi, belum cukup cakap dalam memanfaatkan aplikasi-aplikasi Teknologi Informasi yang bermanfaat dalam menunjang layanan Bimbingan dan Konseling, belum pernah dilakukan pelatihan pengembangan media berbasis Teknologi Informasi terhadap guru Bimbingan dan Konseling di Kota Tarakan. Berdasarkan potensi masalah yang diperoleh, maka dilakukan kolaborasi dalam memberikan pelatihan pengembangan media-media berbasis teknologi informasi sebagai gerakan meningkatkan kecakapan guru dalam memanfaatkan Teknologi Informasi. Program ini diharapkan dapat meningkatkan kualitas layanan Bimbingan dan Konseling. Muaranya adalah memaksimalkan pemanfaatan Teknologi Informasi yang semakin berkembang sebagai penunjang layanan Bimbingan dan Konseling di sekolah. Kegiatan ini mengusung materi pendampingan dalam optimalisasi Microsoft Powerpoint sebagai media ajar dan Penyusunan Assesment Online melalui Google Formulir yang dilaksanakan selama dua hari di Ruang Pertemuan SMP Negeri 1 Tarakan pada Hari Rabu-Kamis, 28-29 Juli 2022.Kata Kunci : Teknologi Informasi, Bimbingan Konseling